Cerebral fat embolism syndrome after long bone fracture: A case report - Mariam Kassimi (Elsevier, 2022)
Cerebral fat embolism is a rare and potentially fatal condition that may occur following a long bone fracture. Its characterized by respiratory, neurological, and mucocutaneous signs. Isolated severe brain syndrome remains exceptional. We report a 21-year-old male patient admitted for the cerebral manifestation of a fat embolism syndrome due to a fracture of long bone after a traffic accident injury. Neurological deterioration after a free interval was seen with generalized tonic-clonic seizures. MRI of the brain was indicated which showed numerous multifocal hyperintensities involving the deep white matter of both hemispheres producing a “starfield” appearance. This pattern of cytotoxic cerebral edema, with lesions in the white matter rather than the grey matter, is indicative of the subacute stage of fat embolism. The patient was treated with comprehensive support in the intensive care unit, he returned to normal neurological function and was discharged after 3 weeks of hospitalization.